PENGARUH MOTIVASI DAN KEMAMPUAN APARAT TERHADAP KUALITAS PELAYANAN PAJAK BUMI DAN BANGUNAN DI DINAS PENDAPATAN DAN PESEDAHAN AGUNG DI KABUPATEN TABANAN, PROPINSI BALI - Sutaya, I Made (JPAP: Jurnal Penelitian Administrasi Publik, 2015)
Credible administration will depend on the extent to which the government's ability toprovide quality public services to the community. Public service is not just a matter ofpolitical policy, and provision of facilities - public facilities, but concerns the services -services provided to the public. With such conditions, we can see how important theposition and role of government bureaucracy or the state apparatus in implementingnational development, among other public services. This study sought to look at theability of the government bureaucracy as a public organization in providing services tothe public. This study attempts to reveal how big a factor - micro organizational factorsis motivation and capability of personnel, especially human resources of the servicequality and Building Tax. Dgunakan method is a quantitative method. Results of theanalysis and findings of the research is that the motivation variable pelyanan have aninfluence on the quality of land and building tax that must be implemented. Comparedwith the motivation variable, the variable capability has significant influence where thelevel of near-perfect correlation shows that the composition of the employee who is onthe Department of Revenue and the Supreme Pesedahan Tabanan Regency sufficient.Keywords: Motivation and Ability, Quality of Service, Tabanan